ESTIMATION OF DIRECT RESPONSE TO TRUNCATION SELECTION OF LITTER SIZE IN LARGEWHITE FLOCK OF SWINE IN MIDWESTERN NIGERIA. - ORHERUATA, A.M.; VAIKOSEN, S.E. (Nigerian Journal of Animal Science, 2023)
Data obtained from the swine records kept between 1982 and 1992 at the Nigerian Institute for Oil Palm Research (NIFOR) were analysed to estimate response to truncation selection by selecting sows with average litter size of 5 and above. Traits analysed were litter size (LITSZ), birth weight (BWT), weaning weight (WWT) and farrowing interval (FRINT). Average value of 6.27 to 6.52(no); 1.44 to 1.46(kg); 5.31 to 5.38(kg) and 217.00 to 242.81(days) and 6.78 to 6.97(no); 1.30(kg); 5.24 to 5.28(kg) and 232.00 to 251.43(days) were obtained for LITSZ, BWT, WWT and FRINT before and after selection respectively. Heritability estimate of 0.13±0.13; 0.25±0.12; 0.15± 0.01 and 0.11± 0.12 were obtained for LITSZ, BWT, WWT and FRINT respectively. Correlation coefficient among the traits was low and not significant with reproduction (FRINT) and LITSZ being negatively correlated. LITSZ, WWT and FRINT showed positive response to selection while BWT ha d negative response. Selection of sows for increased litter size at first parity was as good as using average performance at 1st and 2nd and 1st, 2nd and 3rd parities.